Identifying Women’s Identity in Bhaji on the Beach Film - Suharto, Ririn Pratiwi (Centre for Literary and Cultural Studies, 2023)
Indian is one of the ethnic groups in Britain. The interesting problem of Britain ethnic group is about Indian women. The source of data in this study is Bhaji on the Beach film. It is a Britain comedy drama film. This film shows Saheli Asian Women group. That group consists of the old Indian women and the young Indian women who live in Britain. One day, they have a journey in Blackpool, Birmingham. They have different points of view to express their identities. Based on Stuart Hall’s point of view, this paper analyzes the diasporic identity of Indian women. The qualitative method is used in this study accordingly. The method of analyzing data uses content analysis. The aims of this study are (1) to reveal the characters’ responses about the diasporic identity problem of Indian women and (2) to explain their reasons about their different responses toward the diasporic identity problem of Indian women. The results of this study are (1) the old Indian women show their identities as Indian because they still believe their values system in India and (2) the young Indian women show their identities as British because they are open minded to accept Britain cultural values.